Formulation and Physical Quality Test of Body Lotion of Averrhoa bilimbi L. Extract as Anti-Mosquito Agent for Aedes aegypti - Eryani, Farica; Miryati, Nanda Riztina; Faulatun, Ike Afni; Gifari, M. Arya; Ramadhan, Fajri; Handayani, Sri Seno (Jurnal Pijar Mipa, 2024)
Mosquitoes are one of the vectors with a high disease spread compared to several other types of insects. Making a body lotion from Averrhoa bilimbi L. leaf extract is an effort to reduce the spread of Aedes aegypti mosquitoes. Averrhoa bilimbi L. leaves contain secondary metabolite compounds that can be utilized as natural repellants. This study aimed to test the phytochemical compounds, physical quality and repellant power of the body lotion formula of the Averrhoa bilimbi L. leaf extract. The test results showed that the lotion preparation was stable in organoleptic observation and homogeneity test. Repellant activity against Aedes aegypti mosquitoes was conducted for 5 hours. The highest protection power of lotion with Averrhoa bilimbi L. leaf extract was obtained at 76.92% at 4% extract concentration from three formulas.